The impact of transaction costs in portfolio optimization A comparative analysis between the cost of trading in Peru and the United States - Chavalle, Luc (2019)
Purpose. This paper aims to analyze the impact of transaction costs in portfolio optimization in Peru. The study aims to compare the transaction costs structure applied in Peru with respect to the ones applied in the USA, and over a few dimensions. Design/methodology/approach. The paper opted for an empirical study analyzing the cost of rebalancing portfolios over a set period and dimensions. Stocks have been carefully selected using Bloomberg terminals, and portfolio designed then rebalanced using VBA programming. Over a few dimensions as type and number of stocks, holding period and trading strategy, the behavior of these different transaction costs has been compared. The analysis has been done for four different portfolios. Findings. The paper provides empirical insights about how a retail investor actively trading in Peru can pay up to 14 times more in transaction costs than trading the same portfolio in the USA. These comparatively high transaction costs prevent retail investors to trade in the Peruvian stock market while fueling illiquidity to this market. Research limitations/implications. The paper deals with a limited amount of Peruvian stocks. Researchers are encouraged to test the proposition further, including other dimensions. Practical implications. The paper includes implications for any retail investor that wants to invest in Peruvian stocks, giving an insight about how expensive it is to actively rebalance a portfolio in Peru. Original/value. This paper fulfils an identified need to study how much it costs to actively invest on the stock market in Peru. Doi:  https://doi.org/10.1108/JEFAS-12-2017-0126